Novel association of the obesity risk-allele near Fas Apoptotic Inhibitory Molecule 2 (FAIM2) gene with heart rate and study of its effects on myocardial infarction in diabetic participants of the PREDIMED trial. - Corella, Dolores.; Sorlí, Jose V.; González, José I.; Ortega, Carolina.; Fitó, Montserrat.; Bulló, Monica.; Martínez-González, Miguel Angel.; Ros, Emilio.; Arós, Fernando.; Lapetra, José.; Gómez-Gracia, Enrique.; Serra-Majem, Lluís.; Ruiz-Gutierrez, Valentina.; Fiol, Miquel.; Coltell, Oscar.; Vinyoles, Ernest.; Pintó, Xavier.; Martí, Amelia.; Saiz, Carmen.; Ordovás, José M.; Estruch, Ramón. (2016)
Background: The Fas apoptotic pathway has been implicated in type 2 diabetes and cardiovascular disease. Although a polymorphism (rs7138803; G > A) near the Fas apoptotic inhibitory molecule 2 (FAIM2) locus has been related to obesity, its association with other cardiovascular risk factors and disease remains uncertain.; Keywords: Heart rate, FAIM2, Apoptosis.; Springer Open.